Health and safety issues within artisanal and small-scale gold mining: a case for Penhalonga, Ward 21 Mutasa District, Zimbabwe - Matsa, Mark Makomborero; Mazire, Fortune; Musasa, Tatenda; Defe, Rameck (Routledge, 2021)
This study examined the health and safety issues affecting artisanal and small-scale gold miners in Penhalonga, Ward 21, Mutasa District. A combination of questionnaires, interviews, focus group discussions (FGDs) and direct field observations were employed. Findings from the research revealed that artisanal miners suffered mainly from diseases such as malaria and sexually transmitted infections. Superstitions and myths were among the causes of accidents. Several measures adopted to address health and safety issues, include awareness campaigns, hazard identification and risk assessment. The research recommends that mining claim owners should increase education and awareness on the use of personal protective equipment.